Design Method to Structure Orthosis Design: Camptocormia Postural Brace Case Study. (3rd February 2019) - Duarte, Ricardo; Nadeau, Jean-Pierre; Ramos, Antonio; Mesnard, Michel
Abstract : The orthosis is considered a class 1 medical device which often originates from a nonstructured development process. As these devices are mainly developed by small- and medium-sized enterprises, with no standard research method, the result can be an unadapted device which may not respond to the user's needs and which in the short term may be abandoned. One way to solve this problem is to define and apply standard rules and procedures throughout the development/design process. Although methodologies may solve the "empiricism" in orthosis design problems, these design strategies are not applied during orthosis development due to the particularities of this field and the difficulties in linking the required knowledge and the actors that may be present during the orthosis development. The objective of this work is to develop a methodology to structure the orthosis design process that takes into account both the device life cycle and the different stakeholders involved in the design process. A case study was used to validate the proposed methodology. It was applied to the development of an orthosis to treat a specific postural disorder called camptocormia, also known as bent spine syndrome. This disorder is characterized by the anteroflexion of the trunk and especially affects elderly people. Contrary to scoliosis, the characteristics of camptocormia are not permanent, which means that the patient is able to straighten his posture. A postural brace is used to treat this disorder which enables the patient to redress and maintain the correct upright posture of the trunk.